Effect of accelerated aging of seeds on emergence and field performance of wheat - Schuch, Luis Osmar Braga; Lin, Shiow Shong (Pesquisa Agropecuaria Brasileira, 2014)
This experiment was conducted at the Agronomic Experiment Station of the Federal University of Rio Grande do Sul, Guaíba, RS, Brazil, in 1979. The objective was to study the effect of accelerated aging in three wheat cultivars (Triticum aestivum L.) on seed vigor and the effect of this on emergence and field performance of the resulting plants. The seed vigor decrement caused reduction on field emergence, number of panicle per m2 and seed yield. However, differences in seed vigor did not affect number of tillers per plant, plant height, number of kernels per panicle, 100 kernels weight and weight of hundred liters of kernels.